Membrane associated proteases and their inhibitors in tumour angiogenesis. Issue 6 (27th May 2004) - Noel, A; Maillard, C; Rocks, N; Jost, M; Chabottaux, V; Sounni, N E; Maquoi, E; Cataldo, D; Foidart, J M
Abstract : Cell surface proteolysis is an important mechanism for generating biologically active proteins that mediate a range of cellular functions and contribute to biological processes such as angiogenesis. Although most studies have focused on the plasminogen system and matrix metalloproteinases (MMPs), recently there has been an increase in the identification of membrane associated proteases, including serine proteases, ADAMs, and membrane-type MMPs (MT-MMPs). Normally, protease activity is tightly controlled by tissue inhibitors of MMPs (TIMPs) and plasminogen activator inhibitors (PAIs). The balance between active proteases and inhibitors is thought to determine the occurrence of proteolysis in vivo. High concentrations of proteolytic system components correlate with poor prognosis in many cancers. Paradoxically, high (not low) PAI-1 or TIMP concentrations predict poor survival in patients with various cancers. Recent observations indicate a much more complex role for protease inhibitors in tumour progression and angiogenesis than initially expected. As knowledge in the field of protease biology has improved, the unforeseen complexities of cell associated enzymes and their interaction with physiological inhibitors have emerged, often revealing unexpected mechanisms of action.